The Admission of New Students Based on Online System at SMAN 2 Singkawang - Sularto Sularto; Wahyudi Wahyudi; Sukmawati Sukmawati (JETL (Journal of Education, Teaching and Learning), 2018)
The application of online-based student admission aims to provide the widest possible opportunity for every citizen to obtain a fast, transparent and accountable registration service. The purpose of the research carried out at the State Senior High School 2 Singkawang (SMAN 2 Singkawang) was to describe the online-based prospective student admission planning at SMAN 2 Singkawang, organizing admissions based on online students at SMAN 2 Singkawang, the implementation of prospective participants online-based students at SMAN 2 Singkawang, online admission supervision of prospective students at SMAN 2 Singkawang, as well as an online evaluation of new student candidates at SMAN 2 Singkawang. The approach used in this study is qualitative research on the type of case study research. The results of the research that have been conducted include 1) Planning the recruitment process of online-based prospective students conducted by the agency and the school; 2) Organizing in the acceptance of new students through the division of committee work; 3) Implementation of new online-based student admissions is carried out in accordance with existing technical instructions; 4) Supervision carried out in new student admission activities is carried out by the principal as the head of the education unit and also as the person in charge of the activity; 5) On this online-based new student admission activity, it has run well. But there are those that are the main focus of supporting activities are the internet and electricity networks, so that these two facilities must be ensured in good condition.